Alcohol, smoking, and risk of Her2‐overexpressing and triple‐negative breast cancer relative to estrogen receptor‐positive breast cancer. Issue 8 (26th July 2018) - Baglia, Michelle L.; Cook, Linda S.; Mei‐Tzu, C.; Wiggins, Charles; Hill, Deirdre; Porter, Peggy; Li, Christopher I.
Abstract : Epidemiological evidence is limited on how alcohol consumption and smoking are associated with risk of different subtypes of breast cancer, such as triple‐negative (TN) and human epidermal growth factor receptor 2‐overexpressing (H2E) breast cancers, which may have different etiologies from more common luminal (estrogen receptor [ER+]) breast cancers. In this population‐based case‐case study, we evaluated the association between alcohol, smoking, and risk of H2E and TN breast cancer, compared with ER+ breast cancers, among women aged 20–69 years. Using polytomous regression, associations between alcohol consumption, smoking, and breast cancer risk were evaluated in 909 ER+, 1, 290 TN, and 489 H2E breast cancer patients, with ER+ breast cancer patients as the reference group. Current alcohol consumption at diagnosis was associated with a lower risk of H2E breast cancer (odds ratio = 0.74, 95% confidence interval: 0.58–0.92) relative to ER+ cancers. No difference in association was observed by menopausal status. No association between alcohol consumption and TN breast cancer relative to ER+ breast cancer was observed. Women who smoked did not have an altered risk of TN or H2E breast cancer, relative to ER+ cancer. Our results suggest that alcohol is associated with lower risk of H2E breast cancer relative to ER+ breast cancer. This study adds to the body of epidemiologic evidence that breast cancer etiology differs by breast cancer subtype. Abstract : What's new? Breast cancer comes in many forms, but when looking for risk factors, the less common subtypes get less attention. Here, the authors investigated the effect of smoking and drinking alcohol on the risk of triple‐negative and H2E breast cancers, compared with the more common ER+ cancers. Alcohol consumption, they found, correlated with a lower risk of H2E breast cancer relative to ER+ cancer, but they saw no difference in risk of TN cancer. They also observed no difference in risk from smoking between the three cancer subtypes.